1977
DOI: 10.1007/bf01852114
|View full text |Cite
|
Sign up to set email alerts
|

The vasoconstrictive effect of dopamine in the isolated, perfused rat kidney after catecholamine depletion

Abstract: In the isolated, perfused kidney of untreated and catcholamine-depleted rats (by 6-hydroxydopamine and reserpine), dopamine (DA) caused a dose-dependent increase in vascular resistance which could be prevented by prior blockade of the alpha-adreno-receptors. The DA-induced vasoconstriction thus appears to be due to a direct stimulation of alpha-receptors in the kidney rather than an indirect sympathomimetic effect through release of noradrena-line from local adrenergic nerve terminals. The effectiveness of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1979
1979
1983
1983

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Previously, evidence had been provided for direct T-B cell recognition, both in vivo [3,61 and in other similarly stringent in vitro systems [26]. It should be noted, however, that "nonspecific" soluble factors have, in fact, been found to induce polyclonal Ig secretion without detectable mitogenicity [27].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, evidence had been provided for direct T-B cell recognition, both in vivo [3,61 and in other similarly stringent in vitro systems [26]. It should be noted, however, that "nonspecific" soluble factors have, in fact, been found to induce polyclonal Ig secretion without detectable mitogenicity [27].…”
Section: Discussionmentioning
confidence: 99%
“…Pendleton & Sherman (1976) found that dopamine does cause a diuresis in the rat, but that this depends on an action on ac-adrenergic receptors. Moreover, Aihara, Kasai & Sakai (1972), Neuvonnen & Westermann (1973) and Augustin, Baumgarten, Huland & Leichtwaub (1977) found that infusions of dopamine cause only vasoconstriction in the rat. We have investigated this topic further and evidence is presented in this paper to show that dopamine can have actions on the renal vascular bed of the rat which are similar to those reported for man and dog.…”
Section: Introductionmentioning
confidence: 99%
“…A vasodilator response has also been reported in the intact rat (Greven & Klein, 1977) but not in the cat (Wassermann, Huss & Kullmann, 1980). Studies in the rat isolated perfused kidney have produced conflicting results (Augustin et al, 1977;Woodman & Lang, 1980). In all species dopamine has diuretic and natriuretic effects which can be blocked by specific dopamine receptor antagonists (Wassermann et al, 1980;McGrath & Jablonski, 1981).…”
Section: Introductionmentioning
confidence: 99%